Manifolds and mechanics - Jones, Arthur 1934- (Cambridge University Press, 1987)
This book provides an easy introduction to the theory of differentiable manifolds. The authors then show how the theory can be used to develop, simply but rigorously, the theory of Lanrangian mechanics directly from Newton's laws. Unnecessary abstraction has been avoided to produce an account suitable for students in mathematics or physics who have taken courses in advanced calculus
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Differentiable manifolds; Mechanics, Analytic; Mechanik; Differenzierbare Mannigfaltigkeit